Promoting Agricultural Trade to Enhance Resilience in Africa - Badiane, Ousmane; Makombe, Tsitsi; Bahiigwa, Godfrey (International Food Policy Research Institute, 2014)
The 2013 Annual Trends and Outlook Report (ATOR) contributes to the emerging debate by analyzing Africa’s recent trade performance and future outlook at the global and regional levels, including discussions of the mechanisms of dealing with food price volatility, the scope for increasing trans-border trade, and the potential impacts of weather-related shocks and biophysical factors on intra-regional exports. The ATOR finds that Africa’s share of world trade of goods and services, and specifically of agricultural goods, made a turnaround and started increasing in the 2000s. Also, intra-Africa agricultural exports have grown rapidly in recent years, particularly in calorie terms, thus lessening the continent’s dependence on the West in terms of trade. The Report attributes the improved trade performance to recent improvements in economic growth and infrastructure on the continent, together with higher world prices for some key raw materials.